2013
DOI: 10.1007/s12272-013-0077-7
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic polyketides from a sponge-derived fungus Metarhizium anisopliae mxh-99 and their antitubercular activities

Abstract: In our screening for antitubercular agents, five naphtho-γ-pyrones including two new naphtho-γ-pyrones glycosides, indigotides G and H (1 and 2), and two diphenyl ethers were isolated from the extract of a sponge-derived fungus Metarhizium anisopliae mxh-99. Their structures were established on the basis of chemical and spectroscopic evidence. The antitubercular activities of all the compounds were evaluated against Mycobacterium phlei. The known isochaetochromin B2 (6) and ustilaginoidin D (7) exhibited the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…Isochaetochromin B 2 (6) and ustilaginoidin D (20) isolated from the sponge-derived fungus Metarhizium anisopliae mxh-99 exhibited anti-tubercular activity with MIC values of 50.0 μg/mL [16]. 8'-O-Demethylnigerone (57) and 8'-O-demethylisonigerone (58) from the marine-derived Aspergillus carbonarius also showed weak anti-tubercular activity against Mycobacterium tuberculosis H37Rv with MIC values of 43.0 and 21.5 μM, respectively [7].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Isochaetochromin B 2 (6) and ustilaginoidin D (20) isolated from the sponge-derived fungus Metarhizium anisopliae mxh-99 exhibited anti-tubercular activity with MIC values of 50.0 μg/mL [16]. 8'-O-Demethylnigerone (57) and 8'-O-demethylisonigerone (58) from the marine-derived Aspergillus carbonarius also showed weak anti-tubercular activity against Mycobacterium tuberculosis H37Rv with MIC values of 43.0 and 21.5 μM, respectively [7].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The remaining bis-naphtho-γ-pyrones produced by fungi and their bioactivities need to be further studied. In recent years, an increasing number of bis-naphtho-γ-pyrones have been isolated from endophytic fungi [3,10,20] and marine-derived fungi [7,16,23]. These fungi could be the rich sources of biologically active metabolites that are indispensable for medicinal and agricultural applications [1,[63][64][65][66].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…For example, the biological activities of some NGPs have already been reviewed showing anti-viral, anti-microbial, insecticidal, and anti-estrogenic activities (Barrow and McCulloch 2009;Lu et al 2014). In the search of natural compounds with attractive biological properties, NGPs produced by filamentous fungi were identified within two opposite strategies: (i) screening for a specific activity and elucidation of responsible compounds (Singh et al 2003;Song et al 2004;Shaaban et al 2012;Kong et al 2013) and (ii) biochemical discovery of new family members and testing of their putative anti-microbial properties (Ehrlich et al 1984;Akiyama et al 2003;Bouras et al 2005). An exhaustive list of NGPs produced by filamentous fungi is presented in Table 1, including producer organisms and their described biological properties like anti-HIV, anti-tubercular, anti-hyperuricemia, anti-microbial, anti-tumor, and anti-oxidant, as many biological activities could be valued in pharmaceutical, cosmetic, and food industry.…”
Section: Biological Activities Of Fungal Ngps and Their Potential Indmentioning
confidence: 99%
“…To the best of our knowledge, a diphenyl glycoside was found from a sponge-derived fungus Metarhizium anisopliae [23]. In present study, the diphenyl glycoside derivatives were reported for the first time isolated from coral-derived fungi.…”
Section: Resultsmentioning
confidence: 68%